Hubungan Antara Paritas, Penyakit Infeksi Dan Status Gizi Dengan Status Anemia Pada Ibu Hamil Trimester III - Akhmad Mahyuni; Nirma Yunita; eka maya putri (HB PRESS, 2019)
World Health Organization (WHO) data in 2010 noted 40% of maternal deaths in developing countries are associated with pregnancy anemia. Anemia anemia in pregnancy caused by iron deficiency and acute bleeding, even distance mutually interact with each other. Anemia in pregnancy is a major health problem in developing countries with high morbidity in pregnant women. The average pregnancy with anemia in Asia is estimated at 72.6%. The high prevalence of anemia in pregnant women is a problem that is being exposed to the government of Indonesia. Preliminary study results conducted by researchers through physical examination of pregnant women in third trimester, seen from signs of symptoms, as many as 10 people, there are 6 people (60%) who have anemia and 4 people (40%) were not anemic, of 6 people with anemia there were 3 (50%) unsafe parities, 1 person (16.7%) had infectious diseases, and 2 (33.3%) malnourished. The purpose of this study was to determine the relationship of parity, infectious diseases, and nutritional status with anemia status in third trimester pregnant women in the work area of ​​PuskesmasPasalingHulu Sungai Selatan in 2017. The method used was analytical with cross sectional approach. The result of this research are most of respondents who suffer from anemia that is as many as 33 people (67,3%), unsafe parity that is 29 people (59,2%), not enter as many as 34 people (69,4%), as many as 28 people (57.1%). there is a proven to have relationship of parity, nutritional status with anemia status in third trimester pregnant women in work area of ​​Puskesmas PasungkanHulu Sungai Selatan 2017, not proven to have relation of disease with anemia status in third trimester pregnant woman in working area of ​​Puskesmas PasungkanHuluSungai Selatan 2017 Keywords: Status of anemia, parity, infectious diseases, nutritional status